A Cross-Sectional Study of Hepatitis E Virus Infection in Healthy People Directly Exposed and Unexposed to Pigs in a Rural Community in Northern Thailand - Hinjoy S. (2014)
Summary: A cross-sectional study of the association between occupational pig exposure and hepatitis E virus (HEV) infection in adult pig farmers and the general population who were not directly exposed to pigs was conducted in Nan Province, Thailand, from November 2010 to April 2011. All participants were interviewed to provide information on their job history, eating habits and other potential confounders. The prevalence of anti-HEV immunoglobulin G antibodies (IgG) among 513 subjects was 23.0%. Hand washing with water and soap was associated with a lower seroprevalence of HEV infection, whereas living in an area with frequent flooding (OR 1.64, 95% CI: 1.00-2.68) and consuming internal pig organs more than twice per week (OR 3.23, 95%CI: 1.15-9.01) were both associated with a higher seroprevalence of anti-HEV IgG. There was no association between HEV seroprevalence and frequent, direct occupational pig contact. © 2012 Blackwell Verlag GmbH.